O contexto social da dança na paralisia cerebral: aspectos funcionais e qualidade de Vida - Santos, Graciele da Silva (2017)
Cerebral palsy (CP) is characterized by permanent disturbances in posture, muscle tone and movements, they are accompanied by sensorial deficits, which limit the performance of functional activities. Dance provides physical, emotional and social well-being and allows the inclusion of people with disabilities in the socio-cultural field. This study aims to analyze the effect of dance on functionality, social participation and quality of life in CP youngs. It is a serial cases of seven participants with CP, both genders, whose participated of dance classes, lasting30 minutes, twice a week, every other day, during 16 sessions/classes. The following instruments were used to analize functionality and social participation: Functional Independence Measure (FIM) and World Health Organization of Disability Assessment Schedule (WHODAS), version 2.0, item on social participation. In the Dance group, there were increase in functional independence, especially in personal care (p=0.04), mobility (p=0.01), locomotion (p=0.01), communication (p=0.0004) and social cognition (p = 0.002), and in total MIF values (p=0.0009); in social participation, verified by WHODAS, there was also a difference after the intervention (p=0.045). The dance shows itself as a playful and artistic resource that promote functionality, social interaction and quality of life in CP.